Robotic surgeries: an initial experience in a multispeciality hospital - Bada, Vijaykumar C.; Pavankumar, V.; Kumar, Patwadi Ajay; Reddy, Shilpi; Sasanka, V. (International Surgery Journal, 2020)
Background: The use of robotic surgical systems is an expanding technology in the world. Robot-assisted surgery overcomes some limitations of laparoscopy. Aim was to evaluate a single surgeon’s experience with safety, feasibility, complications, and short- and long-term outcomes for robotic assisted procedures. Methods: It was a prospective study of 39 patients operated by robotic assistance performed 39 surgeries from November 2018 to June 2020 in three departments with follow up of 2 years. The surgeries performed included gastroenterology, gynecological and urological system. Results: It was a prospective, analytical and descriptive study. In total 39 cases in present study followed up for 3 years. Most of the patients in study are in >65 years age group, and females have been operated mostly. Surgeries in our hospital done with robotic assistance ware 13 cases (33.3%) in gastroenterology department, gynecological department with total 17 cases (42.5%) and in urology department it was 9 cases (23.2%). Gastroenterology surgeries took less time of 100 minutes. Blood loss in gynecological surgeries was more compared to other departments with 103 ml followed by urology 98 ml. Hospital stay in present study was less for gynecological surgeries with one day of admission. All over complications are around 2.5%. Success rate in our study was 97.5%. Conclusions: It was concluded that robotic surgery offers an effective and safe alternative in the surgical treatment.